Dampak Perubahan Batas Usia Nikah Terhadap Dispensasi Nikah di Pengadilan Agama - Amina, Siti Nur (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Marriage or what is often called marriage is a common thing done by all humans on earth. In the Qur'an it is stated that living in pairs, living in pairs is the instinct of all creatures of Allah SWT, including humans. In our country, Indonesia, there is a law regarding the age of a person who wants to get married, but the law has been revised, namely in the decision of the Constitutional Court which has amended the marriage law No. 1 of 1974 concerning marriage which states that